2015
DOI: 10.1073/pnas.1418805112
|View full text |Cite
|
Sign up to set email alerts
|

Virus-induced translational arrest through 4EBP1/2-dependent decay of 5′-TOP mRNAs restricts viral infection

Abstract: The mosquito-transmitted bunyavirus, Rift Valley fever virus (RVFV), is a highly successful pathogen for which there are no vaccines or therapeutics. Translational arrest is a common antiviral strategy used by hosts. In response, RVFV inhibits two well-known antiviral pathways that attenuate translation during infection, PKR and type I IFN signaling. Despite this, translational arrest occurs during RVFV infection by unknown mechanisms. Here, we find that RVFV infection triggers the decay of core translation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 76 publications
2
44
1
Order By: Relevance
“…2D; Moy et al 2014b). An endogenous mRNA, hDCP2 (the levels of which are unaffected by RVFV infection) (Hopkins et al 2015), was not significantly bound. Similar results were found for SINV infection, in which SINV genomic and subgenomic RNAs (which function as mRNAs) were significantly bound by hZCCHC7 (Fig.…”
Section: Zcchc7 Specifically Binds Rvfv Mrna and Sinv Rnamentioning
confidence: 92%
See 1 more Smart Citation
“…2D; Moy et al 2014b). An endogenous mRNA, hDCP2 (the levels of which are unaffected by RVFV infection) (Hopkins et al 2015), was not significantly bound. Similar results were found for SINV infection, in which SINV genomic and subgenomic RNAs (which function as mRNAs) were significantly bound by hZCCHC7 (Fig.…”
Section: Zcchc7 Specifically Binds Rvfv Mrna and Sinv Rnamentioning
confidence: 92%
“…RNASEL, which is induced by interferon signaling, nonspecifically degrades both viral and cellular RNA as a step toward cell death (Hassel et al 1993;Castelli et al 1997;Brennan-Laun et al 2014). In contrast, recent studies have shown that 5 ′ exonucleases and decapping machinery selectively target flaviviruses and bunyaviruses, respectively (Hopkins et al 2013(Hopkins et al , 2015Moon and Wilusz 2013). The 3 ′ -to-5 ′ RNA exosome and its associated cofactor complexes have been implicated in some immune functions but are less understood.…”
mentioning
confidence: 99%
“…Additionally, mRNAs that contain 5 -terminal oligopyrimidine tracts (5 TOP) are preferentially translated during bacterial infection to support the high synthesis of pro-inflammatory cytokines [23]. In contrast, viral infection (e.g., mosquito-transmitted bunya virus, Rift Valley fever virus) leads to reduced translation of 5 TOP mRNAs upon mTOR-dependent 4E-BP phosphorylation [24]. Viruses snatch the cap-structure including the 5 TOP to enhance translation of their own mRNAs [25].…”
Section: Mtor Goes For the Topmentioning
confidence: 99%
“…Viruses snatch the cap-structure including the 5 TOP to enhance translation of their own mRNAs [25]. The cell counteracts the viral propagation by preferential degradation of mRNAs bearing 5 TOP motifs [24]. Notably, proteins participating in the translation machinery (e.g.…”
Section: Mtor Goes For the Topmentioning
confidence: 99%
See 1 more Smart Citation